Using document analysis to revise competency frameworks: Perspectives from the revision of competency standards for dietitians - Allen, Louise M.; Palermo, Claire (Frontiers in Medicine, 2022)
Introduction: In resource poor environments, low cost methods are needed to review competency standards to ensure they remain reflective of the current health workforce. This study aims to show how document analysis can be used to inform the revision of competency frameworks and standards. Methods: Altheide and Schneider’s document analysis was modified to revise the National Competency Standards for Dietitians in Australia. This involved an eight-step process: i) define the goal, ii) identify documents for analysis, iii) choose the analysis approach, iv) engage with the documents and perform the analysis, v) draft revisions, vi) stakeholder engagement, vii) final revisions, viii) dissemination. Documents were sought through a combination of literature searches, review of document databases, and targeted document sourcing for documents relevant to contemporary dietetic practice. Framework analysis was used to analyse the data, with the thematic framework including four categories: i) Aboriginal and Torres Strait Islander peoples, ii) Consumer perspectives, iii) Contemporary and future dietetic roles, and iv) Contemporary wording and structure of competency. All included documents were indexed and charted which informed revisions to the standards. Results: Sixty-seven documents were reviewed. Four new competency standards were added to address the skills and attributes required of dietitians to work effectively with Aboriginal and Torres Strait Islander peoples. One competency standard was modified to include an individualised approach as this was deemed important by consumers but not previously included in the standards. The revised standards also place greater emphasis on dietitian’s role in teaching and learning. In addition, there are now multiple standards that refer to advocacy, sustainability is referenced multiple times, a new standard specific to advanced care planning has been included, and their structure and wording was revised to ensure it was contemporary. Conclusion: Using document analysis to revise competency standards offers an efficient and low-cost method to update competency standards in a resource poor environment. This addresses a key issue with competency standards where unless revised frequently they can become rapidly out of date. Further research is needed to learn if document analysis can be used as a method to create rather than revise competency standards.